A comparative study on layered cobalt hydroxides in water oxidation. Issue 3 (19th May 2016) - Leng, Xue; Wu, Kuang‐Hsu; Zeng, Qingcong; Gentle, Ian R.; Wang, Da‐Wei
Abstract: Oxygen evolution reaction has attracted extensive attention in energy conversion and storage technology (e. g. water splitting and rechargeable metal–air batteries). Its sluggish kinetics demands effective electrocatalysts to minimize the reaction barrier. Transition metal (oxy)hydroxides with a layered structure are one of the most active non‐noble electrocatalysts. In this study, we compared the oxygen evolution performance of α‐Co(OH)2, β‐Co(OH)2 and β‐CoOOH. Our results showed that α‐type hydroxide is more active than β‐type with 60 mV lower overpotential at 10 mA/cm 2 and three times higher current density at 450 mV overpotential. The plausible reason of this superior oxygen evolution activity is likely relevant to the large interlayer space in α‐type hydroxide. © 2016 Curtin University of Technology and John Wiley & Sons, Ltd.